Enhancing student competency in risky clinical environments: Evaluating an online education program. (9th November 2018) - Graj, Ella; Sheen, Jade; Dudley, Amanda; Sutherland‐Smith, Wendy; McGillivray, Jane
Abstract : Objective: Trainees across the healthcare sector contend with ubiquitous risk during clinical placement. This has prompted educative action to enhance student competency in unpredictable clinical environments. The objective of this pilot study was to evaluate the impact of Risk Aware, an online blended simulation‐based learning program, upon student preparedness and confidence for clinical placement. Method: A sequential explanatory mixed‐methods design was utilised to evaluate Risk Aware . The Risk Aware program was trialled on 149 first‐year professional psychology postgraduate students across seven Australian universities prior to their first clinical placement. Repeated measures t ‐tests investigated the impact of Risk Aware learning modules upon student knowledge and confidence; descriptive statistics and analysis of frequencies summarised student competency following Risk Aware ( N = 120). Follow‐up qualitative interviews explored the nature of student knowledge and confidence, and student impressions of Risk Aware ( N = 8). Results: Preliminary quantitative findings demonstrated significant increases in student knowledge and confidence ( p < 0.05), and low‐to‐average competence, after Risk Aware . Qualitative results corroborated increases in student knowledge and confidence and pointed to early signs of clinical competency. Student impressions of Risk Aware were generally positive and included suggestions to improve program usability. Conclusions: Findings highlight Risk Aware's capacity to increase students' ability to identify and detail responses to risks arising during placement. Further field testing to ascertain students' application of skills is required. Results will inform program modifications to enhance future Risk Aware iterations.